Mural sebagai Media Kreativitas dan Perbaikan Visual di SMP Negeri 1 Pamboang - Arie Arma Arsyad; Dewi Sartika (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of the service that will be carried out is the creation of a classroom mural with a pattern that depicts the identity of each class to strengthen the creativity of the students of SMP Negeri 1 Pamboang as a visual improvement of the school. The method used in making this mural is to have a discussion with the school regarding the theme that will be depicted on the mural. The implementation of this activity went well as planned. This program activity in the form of making murals gives a new look to the school as well as a medium for developing student creativity.